Pelatihan Pembuatan Laporan Keuangan Bagi Penyandang Disabilitas Pengelola Usaha Kreatif - PINEM, ANWAR ARIFIN; Rahmayuni, Siti (Cahaya Pengabdian, 2025)
This community training program is designed to enhance financial reporting skills for individuals with disabilities who run creative businesses. Many disability-based micro and small enterprises encounter challenges in recording transactions, separating personal and business finances, and preparing simple financial statements, which limits their access to funding and business growth opportunities. The aim of this program is to improve participants' understanding and practical skills in creating basic financial reports, such as cash flow records, income statements, and simple balance summaries. The method used involves participatory training that includes interactive lectures, guided practice, simulation of bookkeeping cases, and direct mentoring sessions tailored to participants’ accessibility needs. The evaluation was carried out using pre- and post-training assessments along with practical exercises. The results demonstrate a significant improvement in participants' comprehension of financial recording concepts and their ability to prepare structured financial reports independently. Participants were able to apply basic bookkeeping tools that are appropriate for the size of their businesses. In conclusion, inclusive and practice-based financial reporting training effectively enhances managerial capacity and supports the sustainability of creative businesses led by persons with disabilities.